2021
DOI: 10.1177/19417381211044736
|View full text |Cite
|
Sign up to set email alerts
|

Eight Weeks of Self-Resisted Neck Strength Training Improves Neck Strength in Age-Grade Rugby Union Players: A Pilot Randomized Controlled Trial

Abstract: Background: Greater neck strength is associated with fewer head and neck injuries. Neck-strengthening programs are commonly burdensome, requiring specialist equipment or significant time commitment, which are barriers to implementation. Hypothesis: Completing a neck-strengthening program will increase isometric neck strength in age-group rugby players. Study Design: A pilot randomized controlled exercise intervention study. Level of Evidence: Level 2. Methods: Twenty-eight U18 (under 18) male regional age-grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 29 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…At present, there is a scarcity of research on the physiological effects of Activate , with a single study investigating this area reporting that under-18 youth rugby players had a 24% increase in cervical spine strength after completing the isometric cervical spine exercises for 8 weeks. 36 A few coaches reported that they used Activate to improve their players’ physical characteristics and movement control. There is a high level of evidence that neuromuscular training programmes, primarily football specific programmes such as the 11+ , can promote both acute and chronic physiological adaptations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is a scarcity of research on the physiological effects of Activate , with a single study investigating this area reporting that under-18 youth rugby players had a 24% increase in cervical spine strength after completing the isometric cervical spine exercises for 8 weeks. 36 A few coaches reported that they used Activate to improve their players’ physical characteristics and movement control. There is a high level of evidence that neuromuscular training programmes, primarily football specific programmes such as the 11+ , can promote both acute and chronic physiological adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high level of evidence that neuromuscular training programmes, primarily football specific programmes such as the 11+ , can promote both acute and chronic physiological adaptations. 37 However, beyond the neck strength study, 36 it is not clear if Activate does induce acute and/or chronic physiological responses. Thus there is a need to investigate if Activate does improve the physical characteristics of youth rugby players given this may facilitate programme implementation (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The two major conclusions from the study were as follows: (1) performing a neck exercise program independently, or as part of a whole-body program, could contribute to lower sports-related head and neck injuries; and (2) near-maximal to maximal loads may be required to induce meaningful changes in neck strength when considering isometric or isotonic neck exercises. 24 An additional study by Peek at al. reflected the ease with which a neck strengthening program can be instituted for soccer players.…”
Section: Formal Isometric Neck Strengthening Programsmentioning
confidence: 99%
“…24 To combat this issue, Attwood et al performed a study with a under age 18 (U18) male soccer team. 24 Athletes performed isometric neck exercises three times per week for 8 wks. These included maximal contraction of the neck in each direction (flexion, extension, left/right lateral flexion) with resistance provided by their own hands.…”
Section: Formal Isometric Neck Strengthening Programsmentioning
confidence: 99%
“…Third, strengthening the neck muscles can minimise head acceleration, reducing the risk of head injuries [ 59 ]. Notably, neck muscles are receptive to short-term training, as demonstrated in professional rugby players [ 59 , 60 ]. However, the effectiveness of neck strengthening on headings is still controversial [ 61 ].…”
Section: Soccer-related Head Traumamentioning
confidence: 99%